The Keap1/Nrf2 Signaling Pathway in the Thyroid—2020 Update - Christina Thanas; Panos G. Ziros; Dionysios V. Chartoumpekis; Cédric O. Renaud; Gerasimos P. Sykiotis (Antioxidants, 2020)
The thyroid gland has a special relationship with oxidative stress. On the one hand, like all other tissues, it must defend itself against reactive oxygen species (ROS). On the other hand, unlike most other tissues, it must also produce reactive oxygen species in order to synthesize its hormones that contribute to the homeostasis of other tissues. The thyroid must therefore also rely on antioxidant defense systems to maintain its own homeostasis in the face of continuous self-exposure to ROS. One of the main endogenous antioxidant systems is the pathway centered on the transcription factor Nuclear factor erythroid 2-related factor 2 (Nrf2) and its cytoplasmic inhibitor Kelch-like ECH-associated protein 1 (Keap1). Over the last few years, multiple links have emerged between the Keap1/Nrf2 pathway and thyroid physiology, as well as various thyroid pathologies, including autoimmunity, goiter, hypothyroidism, hyperthyroidism, and cancer. In the present mini-review, we summarize recent studies shedding new light into the roles of Keap1/Nrf2 signaling in the thyroid.